PENDAPATAN DAERAH TERHADAP PERTUMBUHAN EKONOMI PROPINSI DKI JAKARTA: BELANJA MODAL SEBAGAI PEMEDIASI - IMAN AKHADI (Media Bisnis, 2020)
The objective of this research is to analyze the effect of Capital Expenditures in mediating the relationship between Regional Original Revenue and Profit Sharing Funds (Government Grant) for economic growth in DKI Jakarta Province which is measured based on the value of Gross Regional Domestic Product (GRDP) based on constant 2010 prices. Secondary data on variables comes from data on the realization of the DKI Jakarta Provincial Budget between 2013-2017. This research is a quantitative study using multiple regression analysis methods. The results of the study show that simultaneously, Local Original Income and Profit Sharing Funds have a significant effect on economic growth. Partially, only Regional Original Income has a positive effect on economic growth, whereas the Revenue Sharing Fund does not affect the economic growth of DKI Jakarta Province. The results of subsequent research indicate that Capital Expenditures do not mediate the relationship between Regional Original Revenue and Profit Sharing Funds to the economic growth of DKI Jakarta Province